Meditative introspection promotes the First-person's science of consciousness via intuitive pathways: A hypothesis based on traditional Buddhist and contemporary Monist frameworks - Reddy, J. Shashi Kiran; Pereira Jr, Alfredo [UNESP]; Leite, Edilene de Souza [UNESP]; Roy, Sisir (Elsevier B.V., 2020)
What forms the basis for validating any knowledge? Should it be always verified based on the objective and analytical methods that we adapt according to our progressive advancements in science or is there any other way of conceiving knowledge? This is the context where modern sophistication should embrace an ancient perspective. Recently, there have been great advancements in the science of consciousness and meditation. Meditation received much attention as a practice for wellbeing and as a tool for cognitive enhancement. Even though, hundreds of objective studies have been conducted on different practices of meditation across different traditions, there is one essential element missing in almost all of these studies: the discussion of the subjective experience of meditation. Embracing the traditional insights on meditation, we study this element by defining meditation based on the concept of introspection. In addition, we hypothesize that introspective meta-awareness associated with the non-conceptual experience of meditation may result in the conceptual understanding of natural phenomena via pathways of intuition. The proposed advancement bears implications for the ontological and epistemological basis of experiential knowledge, as well as, for developing introspection and meditation-based interventions for self and consciousness disorders.
Keywords: Introspection; Meditation; Intuition; Consciousness; Meta-awareness; First-person; Feeling; Triple-aspect Monism